2017
DOI: 10.3892/etm.2017.4859
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin alleviates iodinated contrast media-induced cytotoxicity in human proximal renal tubular epithelial cells

Abstract: Abstract. Contrast media (CM)-induced nephropathy (CIN) is a serious complication of intravascularly applied radiocontrast media. At present, no drugs have been approved for the prevention of CIN. The present study aimed to explore the effects and potential mechanisms of atorvastatin on iodinated CM-induced cytotoxicity in the human proximal renal tubular epithelial cells. The cytotoxic effect of iohexol (50, 100 and 200 mg I/ ml) and the protective effect of atorvastatin pretreatment (1, 20 and 40 µM) were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Taken together, based on previous study [19] and our experimental results, both iohexol and iodixanol caused mitochondrial damage, autophagy, and mitophagy. However, iohexol induced more markedly decrease in cell viability than iodixanol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, based on previous study [19] and our experimental results, both iohexol and iodixanol caused mitochondrial damage, autophagy, and mitophagy. However, iohexol induced more markedly decrease in cell viability than iodixanol.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous study [19], we select the concentration of 200 mg iodine/ml of iohexol or iodixanol and treatment duration of 6 h for further study on mitochondrial damage and ROS generation. The exposure of iohexol or iodixanol led to a significant increase in the signals of fluorescent MitoSOX, suggesting a reinforcement in ROS production (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodinated radiographic contrast media also increased cytotoxicity in human proximal renal tubular epithelial cells [ 32 , 33 ]. Other authors showed that iodinated radiographic contrast media caused severe and prolonged oxidative stress in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cell treatment. HK-2 cells were incubated in FBS-free DMEM/F12 for 12 h. The establishment of a damaged cells model was performed as previously reported (11). 3-MA (10 mM) was used to inhibit the formation of autophagosomes.…”
Section: Methodsmentioning
confidence: 99%